Global epidemiology and changing clinical presentations of invasive meningococcal disease: a narrative review. Issue 1 (2nd January 2022) - Deghmane, Ala-Eddine; Taha, Samy; Taha, Muhamed-Kheir
Abstract: Neisseria meningitidis (the meningococcus) causes significant morbidity and mortality worldwide through an epidemic or sporadic invasive infections. The epidemiology of N. meningitidis is changing and unpredictable. Certain emerging meningococcal genotypes seem to be associated with increasing unusual clinical presentations. Indeed, early symptoms may vary and are frequently non-specific. However, atypical clinical forms including abdominal presentations, septic arthritis, and bacteremic pneumonia may lead to misdiagnosis and some are usually associated with higher case fatality rates due to delayed optimal management. Improving awareness of clinicians and public health specialists about these unusual but potentially severe presentations should help establish prompt diagnoses and provide appropriate management of cases. In this review, we described unusual panels of clinical presentations of invasive meningococcal disease linked to the recent changes in meningococcal epidemiology.